Quality of life in children with congenital heart disease after cardiac surgery - Sindy Atmadja; Tina Christina Tobing; Rita Evalina; Sri Sofyani; Muhammad Ali (Paediatrica Indonesiana, 2017)
Background Major achievements in congenital heart disease (CHD) treatment over the past 20 years have altered the course and prognosis of CHD. Improvement of quality of life (QoL) is now a major goal of CHD treatment. Objective To assess the QoL in children after cardiac surgery for CHD. Methods A cross-sectional study was performed in children aged 2 to 18 years. The case group had 20 children with a history of corrective heart surgery in the 12 months prior to the study. The control group had 20 healthy children, age-matchedÂ to the case group. The QoL of both groups was assessed by Pediatric Quality of Life Inventory (PedsQL) Generic Core Scales. The same post-operative children were also assessed with the PedsQL Cardiac Module. Data were analyzed using T-test with P < 0.05 as the level of significance. Results This study recruited 40 subjects: 20 post-operative and 20 healthy children. PedsQL Generic Core Scales assessment showed significant differences between groups in the physical function parameter of QoL (P<0.05) in children aged 13-18 years, but there were no significant differences in the social, emotional, and school function parameters. In children aged 2-12 years, there were no significant differences in physical, social, emotional, or school parameters. The PedsQL Cardiac Module assessment revealed that 35% of post-operative children was at risk for physical appearance problems, 80% was at risk for anxiety problems, 40% was at risk for cognitive problems, and 80% was at risk for communication problems. Conclusion Thirteen to 18-year-old children with non complex CHD have poorer physical function than healthy children. Post operative children are at risk for physical appearance, anxiety, cognitive, and communication problems.